IMPLIKASI PERAN BABINSA DALAM KEGIATAN DETEKSI DINI GUNA PENCEGAHAN TERORISME TERHADAP KETAHANAN WILAYAH - Gatot Subagya; Akhyari; Muryanto; Herdin Yudha Puspita (PPM Sdirjianbang Akademi Militer, 2023)
The aims of this study is to determine the implications of carrying out Babinsa's role in early detection activities to prevent terrorism for regional resilience in Sukoharjo Regency based on public perceptions. The research was conducted in the Kodim 0726/Sukoharjo area. The results showed that (1) Babinsa's role as a Regional Command Unit figure in Sukoharjo Regency was able to encourage Village/Kelurahan government officials and all elements of society by carrying out Territorial Development according to the Danramil's instructions. (2) Implications of implementing Babinsa's role in early detection activities to prevent terrorism for regional resilience of Sukoharjo Regency based on public perception (a) Ideological Aspect, expected to be an effort to prevent the spread of Radicalism and Terrorism in order to maintain regional ideological resilience (b) Political Aspect, expected be an effort to increase regional political resilience so as to prevent the occurrence of majority dictators and minority tyranny (c) Economic Aspect, a sense of community security that can be created by officers so that economic activities will continue to grow and develop well in the Sukoharjo region (d) Socio-Cultural Aspects, early detection activities in order to prevent terrorism against the resilience of the Sukoharjo Regency region to prevent threats to inter-religious harmony in Sukoharjo (e) Defense and Security Aspects, in several areas Babinsa has not received full support from the community, the proof is that in overcoming security disturbances Babinsa moves alone without any community support.